(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Udaipur is a big treasure trove of mineral of indescribable qualities. Rajasthan is blessedwith 79 varieties of minerals. Markedly the area of under mining is approximately 1,846 sq. km. which isonly 0.54 of total land cover in the Udaipur. The Udaipur has virtual monopoly in the production ofminerals like Lead-Zinc, Gypsum, Soap Stone, Ball Clay, Calcite, Rock Phosphate, Feldspar, Copper,Jasper, Garnet, and Silver etc. The Udaipur is proud to possess huge reserves of Lignite, Crude Oil andHigh Quality Gas. It is also renowned for its deposits of Marble, Sand Stone and some unique decorativestones. Mining is not only a major source of employment in the rural and tribal area of the Udaipur, butalso a major source of revenue to the Government and minerals playing an important role in thedevelopment of the Udaipur. In this context, this paper covers deposits of various minerals, mineral fuelsand their position in Udaipur.